1983
DOI: 10.1001/jama.1983.03340010031024
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death After Kidney Transplantation

Abstract: Durtng the five-year period September 1074 through August '1979"two to the many physicians outside transhundred nine consecutive patients rec,lved their first kidney transplant In plant ~nterswho are now caring for Denver. During 2.5 to 7.5' years of foDow-up. 54 paUents (28%) died. kidney transplant patients. Infection was the leading cause of death during .. Interval. and was METHODS re.ponslble for 22 (41%) of the 54 deaths. Pneumonia was prtmarUy We, have reviewed the results of 209 re.ponslble for 14 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
3

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 22 publications
1
17
3
Order By: Relevance
“…(3) Although the incidence of pneumonia is lower for kidney transplantation than all other organ grafts, pneumonia is a common and serious infectious complication in renal transplant recipients (RTRs), possibly leading to respiratory failure, with mortality rates of up to 50%. (4)(5)(6) In part due to their frequent contact with the healthcare system and immunosuppressive status, RTRs may have more resistant organisms, thus leading to the potential development of more fulminant and virulent pneumonia in these patients. While the development of novel immunosuppressive drugs has decreased the risk of acute rejection and improved long-term outcome, a lack of drug management and immune modulation has been reported to result in severe infectious conditions in RTRs.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Although the incidence of pneumonia is lower for kidney transplantation than all other organ grafts, pneumonia is a common and serious infectious complication in renal transplant recipients (RTRs), possibly leading to respiratory failure, with mortality rates of up to 50%. (4)(5)(6) In part due to their frequent contact with the healthcare system and immunosuppressive status, RTRs may have more resistant organisms, thus leading to the potential development of more fulminant and virulent pneumonia in these patients. While the development of novel immunosuppressive drugs has decreased the risk of acute rejection and improved long-term outcome, a lack of drug management and immune modulation has been reported to result in severe infectious conditions in RTRs.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic renal failure (CRF) may have cardiovascular problems as a result of chronic anemia, hypertension, patent arte riovenous Fistula and excess of liquids and electrolytes [1][2][3]. In addition, left ventricular hypertrophy (LVH), usually present in these patients is an independent risk factor for car diovascular morbidity and mortality [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that more than 50% of transplanted patients suffer from anxiety, even some years after trans plantation [ 1,2], In one consecutive series of transplant recipients, 15% were claimed to have committed suicide within the follow-up period [3]. Several studies have reported that transplanted patients fare no better than those on dialysis in terms of quality of life [4] or prevalence of minor psychiatric morbid ity [5].…”
Section: Introductionmentioning
confidence: 99%